FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - SUCI WAHYULIZA; NURFTRIYENNY NURFTRIYENNY (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
The purpose of this study is to determine the influence of factors, in this case debt and dividend policies, on firm value in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange during the period 2018 to 2022. The research technique used used is associative research. This research uses secondary data. The data analysis method used in this study is multiple linear regression analysis. The results of this study indicate that partially and simultaneously debt and dividend policies have a positive and significant effect on firm value